Sickle cell disease related mortality in Brazil, 2000–2018 - Augusto Hasiak Santo (Hematology, Transfusion and Cell Therapy, 2022)
Introduction: There is a demand to update national mortality trends data related to sickle cell disease (SCD) in Brazil. This study describes causes of death and mortality issues related to SCD using the multiple-cause-of-death methodology. Methods: The annual SCD mortality data was extracted from the public databases of the Mortality Information System by researching deaths in rubric D57 “sickle-cell disorders” of the International Classification of Diseases, Tenth Revision and processed by the Multiple Cause Tabulator. Results: From 2000 to 2018 in Brazil, a total of 9817 deaths related to SCD occurred during the 19-year period, as the underlying cause in 6924 (70.5%) and as the associated cause of death in 2893 (29.5%). The mean and median ages at death during the entire period were significantly lower for males, 29.4 (±19.6) and 27.5 (15.5–41.5), respectively, than for females, 33.3 (±20.3) and 31.0 (19.5–46.5), respectively. The leading SCD overall associated causes of death were septicemias (32.1%), followed by pneumonias (19.4%) and respiratory failure (18.2%). On certificates with SCD as an associated cause, the underlying causes of death were circulatory system diseases (8.7%), followed, in males, by digestive system and infectious diseases and respiratory system failures, while in females, maternal deaths, included in the chapter on pregnancy, childbirth and the puerperium, accounting for 4.6% of female deaths, were succeeded by digestive system and infectious diseases. Conclusion: This study revised mortality data on death rate trends, underlying and associated causes of death, age at death and regional distribution of death in Brazil.